Peran Pendidikan Anti Korupsi dalam Membentuk Kesadaran Etis Mahasiswa di Perguruan Tinggi - Nisa Wening Asih Sutrisno (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Corruption is not only a legal issue but also reflects a lack of integrity and ethical awareness. Universities have an important role in preparing students who are not only academically capable but also responsible and committed to ethical values. This study aims to analyze the role of Anti-Corruption Education in shaping students’ ethical awareness in higher education. This research uses a qualitative approach through a literature review method. Data were collected from regulations, official documents, anti-corruption education materials, and relevant scientific articles. The findings show that Anti-Corruption Education helps students understand corruption, develop integrity values, recognize academic misconduct, and encourage honest behavior. However, its effectiveness depends on learning methods, lecturers’ role models, institutional policies, and a supportive academic culture. Therefore, Anti-Corruption Education should be implemented through contextual and continuous learning to build students’ ethical awareness and strengthen integrity in university environments.